Effect of Germination and Fermentation of Pearl Millet on Proximate, Chemical and Sensory Properties of Instant "Fura"- A Nigerian Cereal Food - Inyang, C.U.; Zakari, U.M. (Pakistan Journal of Nutrition, 2007)
The study examined the effect of the germination and natural fermentation on the quality of instant "fura"-(a Nigerian cereal food). Pearl millet (Pennisetum glaucum) seeds were soaked for 12 h at room temperature (32±2°C) and sprouted for 48h at the same temperature. The sprouted seeds were washed, dried and milled into flour. The flour was divided into two portions, the first was allowed to ferment naturally at room temperature for 48h and used to produce germinated and fermented fura (GFF). The second portion was used for the production of Germinated Fura (GF). The cleaned, ungerminated grains were milled and the flour also divided into two portions. The first portion was wetted, fermented and used to produce Fermented Fura (FF). The second portion was used to produce Traditional Fura (TF). Standard assay procedures were used to evaluate the fura samples for nutrient composition and phytic acid levels. Germination and fermentation increased the protein, ash, crude fibre, phosphorus, calcium and iron levels of the fura samples. The phytic acid levels were significantly reduced (p